Information and communications technology (ICT) and agricultural extension in developing countries - Spielman, David J.; Lecoutere, Els; Makhija, Simrin; Van Campenhout, Bjorn (Annual Reviews, 2021)
With new possibilities offered by information and communications technology (ICT), an abundance of products, services, and projects has emerged with the promise of revitalizing agricultural extension in developing countries. However, a growing body of evidence suggests that not all ICT-enabled extension approaches are equally effective in improving adoption, productivity, income, or welfare outcomes. In this review, we explore various conceptual and methodological threads in the literature on ICT-enabled extension in developing countries. We examine the role of multiple impact pathways, highlighting how ICTs influence behaviors and preferences, gender and intrahousehold dynamics, spillovers, and public worker incentives. We also explore the opportunities presented by ICT-enabled extension for increasing the methodological rigor with which extension outcomes are identified. These conceptual and methodological insights—coupled with empirical evidence from prior studies—offer direction for several lines of policy-relevant research on ICT-enabled extension.